The impact of the Saudi-British dispute on the borders of the Buraimi region on the interests of American oil companies 1933-1954 - Mohammed Taher, Ayhan (Humanities Journal of University of Zakho, 2021)
Border disputes arose in the Gulf region after the discovery of oil there, and one of the dispute was on the Buraimi region among the Kingdom of Saudi Arabia, the Emirate of Abu Dhabi, the Sultanate of Muscat and Oman, and the year 1933 was identified as the beginning of the search, because it was the year in which the American Standard of California company obtained an oil concession in Saudi Arabia, and the year 1954 was the year when the research ended, and it is the year in which Britain and the Kingdom of Saudi Arabia reached an agreement, according to which the dispute is referred to an international arbitration board for a consideration and a solution. The subject of the research period witnessed important developments after the entry of the American oil companies to the Gulf, and their competition with British oil companies in areas that have border disputes, and its reflection on the positions of the American and British governments, and their attempts to end these disputes and find appropriate solutions to them while preserving their oil interests.